EFEKTIVITAS METODE RED FLAGS DALAM MENDETEKSI KECURANGAN PELAPORAN KEUANGAN ( Studi Komparasi Terhadap Persepsi Internal dan Eksternal Auditor di Wilayah Pekanbaru ) - Indri, Aprilesti; Hard, Hard; Pipin, Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study examines how the different internal and external perceptions ofauditors in the Pekanbaru Region on the effectiveness of the red flags method indetecting fraudulent financial reporting in companies. Respondents in this studywere auditors who worked in Riau Provincial BUMD, BUMN, and PublicAccounting Firm in Pekanbaru. The number of auditors who were sampled in thisstudy were 56 auditors. The method of determining the sample used waspurposive sampling, data collection techniques with questionnaires, and theresearch method used was the Independent Sample T-test on the IBM SPSSversion 22 program. The results of this study indicate a different perception insome indicators of red flags which are divided into 5 dimensions of red flags infraud pentagon theory, namely: pressure, opportunity, rationalization,competence, and arrogance. Where the overall external auditor considers redflags to be more effective in detecting fraudulent financial reporting in thecompany and from the 5 dimensions of red flags, opportunity dimensions areconsidered the most effective.Keywords : Red Flags, Fraud Pentagon Theory, Internal Auditors, ExternalAuditors.